2000
DOI: 10.1021/ed077p1435
|View full text |Cite
|
Sign up to set email alerts
|

How Can an Instructor Best Introduce the Topic of Significant Figures to Students Unfamiliar with the Concept?

Abstract: Students unfamiliar with the concept of significant figures have difficulty making sense of this concept when put in the role of passive note-takers recording lists of rules. The focus of this paper is how best to introduce the concept of significant figures so that students find it meaningful before a stage is reached at which they become turned off. The approach described begins with measurements students are already familiar with from their life experiences and involves the students as active learners. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…George W. Bush was born on July 6, 1946, which was approximately Julian date 2,432,008. 1 For a class discussion held September 1, 2004 (JD 2,453,250), Mr. Bush would be approximately 21,242 days old or 58.157 years. The instructor could use this value to reveal an increasingly precise age in years (i.e., one more decimal place for each successive calculation) for Mr. Bush to allow students to calculate the age in days with increasing precision as outlined in Table 1.…”
Section: Example and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…George W. Bush was born on July 6, 1946, which was approximately Julian date 2,432,008. 1 For a class discussion held September 1, 2004 (JD 2,453,250), Mr. Bush would be approximately 21,242 days old or 58.157 years. The instructor could use this value to reveal an increasingly precise age in years (i.e., one more decimal place for each successive calculation) for Mr. Bush to allow students to calculate the age in days with increasing precision as outlined in Table 1.…”
Section: Example and Discussionmentioning
confidence: 99%
“…Many students will likely learn the rules by rote, but not necessarily understand the rationale and meaning. Some useful approaches have appeared in this Journal to assist students with the uncertainty of measurements and the necessity of significant figures through exercises (1) and activities (2). Herein is an alternative, requiring little preparation and no equipment, that allows students to intuitively discover and discuss the uncertainty of measurements and conversion factors and the necessity of significant figures.…”
mentioning
confidence: 99%
“…If no calibration is specified for the device, it is common practice to assume that the last digit reported is imprecise, i.e., the measurement is reported as plus/minus one in the final digit. This practice accounts for device resolution and operator precision and is borrowed from what is frequently taught in chemistry education (Pacer 2000;Terezakis 2010). In addition, reporting measurements as an interval of plausible values reiterates or alludes to the idea behind confidence intervals.…”
Section: Lecture 1: Measurement Errormentioning
confidence: 99%
“…Research has shown that incorporation of scientific practices into a learning environment promotes the development of expert-like thinking in students, and the chemistry laboratory is the ideal place for students to practice and evaluate their own data. Several laboratory exercises have been developed for exploring the correct use of significant figures through length measurements and for understanding experimental errors through density , and mass determination. Nevertheless, many students struggle to explicate experimental errors in their own data.…”
Section: Introductionmentioning
confidence: 99%